My mother has her “holy trinity”. Growing up in a Polish family on emigration in Australia - Walulik, Anna (Biografie rodzinne i uczenie się: Tom 8, 2021)
The issue matters of the family biographies comprises in a specific way the processes of upbringing in family on emigration. The article focuses on the analysis and interpretations of narrative on the sun’s and father’s life – Poles connected with the emigration to Australia. From them the peculiar character of the trajectory of upbringing processes. This character designates: molding the identity, religious upbringing, and education. The interpretation of the distinguished categories justifies the thesis that the aim of upbringing in family (and not only) is the child’s happy life (adult’s as well). This article shows that man needs transparent points in the following dimensions: historical, psychological, moral, and spiritual to feel happy. His/her attitude to them decides whether the principles coming from the pedagogy of continuity or the radical change are applied in the processes of upbringing. In this context, it can be claimed that the reflective evaluation can serve the assessment of justification of their use in practice.